Instrumen Self-Asessment Berbasis Self-Regulated Learning untuk Penilaian Keterampilan Dasar Mengajar Mahasiswa - Bagus Cahyanto; Mohammad Afifulloh (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: Self-assessment has a strategic role to identify student achievement and learning development independently. This study aims to develop a self-assessment instrument based on self-regulated learning for the Basic Teaching Skills course through the Borg & Gall R&D model which has been adapted according to the needs of this study. The research data were collected using a questionnaire technique and field notes for expert validation and user testing which were analyzed using quantitative and qualitative descriptive techniques. This self-assessment instrument based on self-regulated learning was developed by considering the results of the needs analysis that had been done previously. The results of the development of the instrument show that the self-assessment instrument based on self-regulated learning has been tested by an assessment expert for the Basic Teaching Skills course. Based on the results of the test of validity, reliability, and expert test, it shows that the instrument has had very decent qualifications. In addition, the results of the user test show that the product is very feasible to be used as an assessment instrument for learning in the Basic Teaching Skills course. From the test results, it is found that according to the user (student) this self-assessment instrument based on self-regulated learning is very useful for knowing learning achievement, especially in teaching practice. In addition, this self-assessment instrument can also help students find out the problems of learning independently. Abstrak: Self-asessment memiliki peran strategis untuk mengidentifikasi prestasi dan perkembangan belajar mahasiswa secara mandiri. Penelitian ini bertujuan untuk mengembangkan instrumen self-asessment berbasis self-regulated learning untuk matakuliah Keterampilan Dasar Mengajar melalui model R&D Borg & Gall yang telah diadaptasi sesuai kebutuhan pada penelitian ini. Data hasil penelitian dikumpulkan dengan teknik kuisioner dan catatan lapangan untuk validasi ahli dan uji pengguna yang dianalisis dengan teknik deskriptif kuantitatif dan deskriptif kualitatif. Instrumen self-asessment berbasis self-regulated learning ini dikembangkan dengan mempertimbangkan hasil analisis kebutuhan yang telah dilakukan sebelumnya. Hasil pengembangan instrumen menunjukkan bahwa instrumen self-asessment berbasis self-regulated learning telah teruji dari ahli penilaian untuk matakuliah Keterampilan Dasar Mengajar. Berdasarkan hasil uji validitas, reliabilitas, dan uji ahli menunjukkan bahwa instrumen telah memiliki kualifikasi sangat layak. Selain itu, hasil uji penguna menunjukkan bahwa produk sangat layak untuk digunakan sebagai instrumen penilaian untuk pembelajaran pada matakuliah Keterampilan Dasar Mengajar. Dari hasil uji coba diperoleh hasil bahwa menurut pengguna instrumen self-asessment berbasis self-regulated learning ini sangat bermanfaat untuk mengetahui pencapaian belajar khususnya pada praktik mengajar. Selain itu, melalui instrumen self-asessment ini juga dapat membantu mahasiswa mengetahui permasalahan belajar secara mandiri.